Empowering the Tambakrejo Area Community as a Smart and Disaster Resilient Village in Semarang City - Nana Kariada Tri Martuti; Isti Hidayah; Wahid Akhsin Budi Nur Sidiq; Danang Dwi Saputro; RR. Sri Ratna Rahayu (Universitas Negeri Semarang, 2024)
Tambakrejo Village is one of the areas in Semarang City that is often affected by flooding, administratively it is included in Gayamsari District. Being in a coastal area with an elevation close to sea level means that the Tambakrejo District area has the risk of flooding and tidal problems, where tidal disasters have so far submerged more than 2.5 hectares of land with 25 residents' houses lost. Flood and tidal conditions directly or indirectly affect all aspects of people's lives. The impact of disasters results in damage to facilities and infrastructure, disruption of social activities, education and public health. If this continues, it is feared that it will increase community vulnerability and decline. The aim of the DPIK program is to increase community capacity to have the independent ability to adapt in facing potential disasters and other impacts of climate change, through the Smart and Disaster Resilient Village movement.